Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijerph19063468
|View full text |Cite
|
Sign up to set email alerts
|

“Precious Time Together Was Taken Away”: Impact of COVID-19 Restrictive Measures on Social Needs and Loneliness from the Perspective of Residents of Nursing Homes, Close Relatives, and Volunteers

Abstract: During the COVID-19 outbreak in March 2020, restrictive measures (e.g., prohibiting physical visits and group activities) were introduced in nursing homes to protect older residents. Although the importance of social contacts and social activities to fulfill social needs and avoid loneliness is known, these were challenged during the pandemic. This qualitative study specifically focused on how residents, close relatives, and volunteers in nursing homes experienced the restrictive measures in retrospect and gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 40 publications
3
15
0
2
Order By: Relevance
“…Our findings point to the need for training on the barriers to resident participation in the news media, including handling consent and communicating with residents living with cognitive impairment. The findings from our study also align with other studies that have demonstrated the negative impact of COVID-19 isolation measures on residents’ social needs ( Kyler-Yano et al, 2022 ; Noten et al, 2022 ). The potential for civic and news media exclusion should be acknowledged as policies in residential care are reshaped following the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings point to the need for training on the barriers to resident participation in the news media, including handling consent and communicating with residents living with cognitive impairment. The findings from our study also align with other studies that have demonstrated the negative impact of COVID-19 isolation measures on residents’ social needs ( Kyler-Yano et al, 2022 ; Noten et al, 2022 ). The potential for civic and news media exclusion should be acknowledged as policies in residential care are reshaped following the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Several quantitative studies have concluded that the implications of the pandemic for NH residents were severe in terms of illness and death (Thompson et al, 2020), loneliness and reduced wellbeing (Levere et al, 2021;Van der Roest et al, 2020), worsening of physical health (Levere et al, 2021) and increased use of medication, for example, psychotropics and antidepressants (Campitelli et al, 2021;Stall et al, 2021). Previous qualitative studies including residents and/or their family members support several of these findings and show that the residents suffered from loneliness and unmet social needs (Lood et al, 2021;Noten et al, 2022), as well as grief, stress and deterioration in physical abilities and cognitive functioning (Paananen et al, 2021). Other qualitative studies have examined the impact of the pandemic on health and wellbeing among NH staff, as well as on working practices in NH (Hanna et al, 2022;Hoedl et al, 2022;Sarabia-Cobo et al, 2021;Yau et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Die präsentierten Daten verdeutlichen, dass die Lebenswelten der befragten Pflegeheimbewohner*innen im ersten Lockdown und im Sommer 2020 von emotionaler Einsamkeit und Sorgen geprägt waren, denn die Mehrheit der Befragten gibt an, sich Sorgen über das Virus zu machen und sich emotional einsam zu fühlen. Die Daten entsprechen anderen Ergebnissen qualitativer Forschung über die Auswirkungen der Pandemie auf Bewohner*innen von stationären Pflegeeinrichtungen [ 5 , 14 , 19 ]. Allerdings gab in der vorliegenden Studie auch eine recht große Gruppe der Befragten an, nicht sozial oder emotional einsam zu sein (74 und 39 %) und sich auch keine Sorgen über COVID-19 zu machen (43 %).…”
Section: Diskussionunclassified
“…Die vorhandenen Studien weisen v. a. ein qualitatives Design auf, und ihre Ergebnisse zeigen, dass die pandemiebedingten Einschränkungen bei Pflegeheimbewohner*innen zur Verringerung der Lebensqualität sowie zur Verstärkung von Depression und Angst geführt haben [ 14 ]. Bewohner*innen berichten von Angst und Einsamkeit, die v. a. durch fehlende soziale Kontakte zu nahestehenden Personen und fehlende soziale Aktivitäten verstärkt wird [ 19 ]. In der Publikation einer weiteren Studie wird beschrieben, dass sich die sozialen Beziehungen durch die Einschränkungen deutlich gewandelt haben sowie neue Unsicherheiten und Ängste erlebt wurden [ 8 ].…”
Section: Introductionunclassified